THE ANALYSIS OF FACTORS AFFECTING FIRM PERFORMANCE - Sari, Indah Sekar (Emerging Markets : Business and Management Studies Journal, 2019)
The objective of this research was to analyze the influence of institutional ownership, independent commissioner, audit committee, board size, return on equity, leverage, earnings quality and long term debt as independent variables to support firm performance as dependent variable in listed Indonesia manufacturing companies. Population of this research was all listed manufacturing companies in Indonesia Stock Exchange from 2014 to 2016. The samples are obtained through purposive sampling method which 62 listed manufacturing companies in Indonesia Stock Exchange have met the sampling criteria that resulted in 186 available data that can be used for research. Multiple linear regression and hypotheses test were used as the data analysis method for this research. The result of this research showed that two variables which were return on equity and earnings quality have influence on firm performance of listed manufacturing companies in Indonesia. In a contrary, institutional ownership, independent commissioner, audit committee, board size, leverage, and long term debt do not have influence on firm performance of listed manufacturing companies in Indonesia during the research period.